PENGARUH PENAMBAHAN SUPLEMEN ORGANIK CAIR (SOC)® DAN LAMA PENYIMPANAN TERHADAP DERAJAT KEASAMAN (pH) DAN KUALITAS FISIK PADA SILASE BATANG PISANG (Musa paradisiaca L.) - Achmad Jaelani; Tintin Rostini; Misransyah Misransyah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2018)
Banana stem is one of the potential wastes of pertania for animal feed. The purpose of this study was to analyze the effect of addition of (SOC)® on the degree of acidity (pH) and Physical Quality at Banana Stage Silage. The research method used in this research is an experimental method using Randomized Complete Design (RAL). Treatment of SOC at concentration 0% (Control), 0,1%, 0,2%, 0,3% and 0,4% with storage time consist of 1, 3, 5 and 7 day with replication 4 times. The number of samples used are 80 samples used for pH and physical quality (Color, Odor, Texture and Mushroom Existence). The treatment given in the sample is P0 = 0% SOC (control), P1 = SOC concentration 0.1%, P2 = SOC concentration 0.2%, P3 = SOC concentration 0.3% and P4 = SOC concentration 0.4%. The results showed that the addition of SOC and Lama of storage significantly affect the pH value and the smell of banana tree silage. The best concentration is 0.3% and 0.4% with the best storage time of 5 and 7 days.